INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANJARMASIN - Normajatun Normajatun; Murdiansyah Herman (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
This study aimed to find out the description : the satisfaction of society’s response to public service as well as service quality index value and the performance of the public service in the Departement of Civil Registration and Population of the City of Banjarmasin. The research using survey method and descriptively. Data collection using the questionnaire for respondents whit a simple technique random sampling. Descriptive data analysis with quantitative. The results showed the public generally satisfied with public service provided by the Departement of Civil Registration and Population of the City of Banjarmasin. The quality of service of the Departement of Civil Registration and Population are include in categories B, and the performance of his ministry is in good category either.